KAJIAN KASUS HUBUNGAN POLA ASUHAN GIZI, PENGETAHUAN GIZI IBU PEKERJA SEKS KOMERSIAL DENGAN STATUS GIZI PADA ANAK BADUTA (Studi di KompleksLokalisasiTegalrejo, KecamatanBergas, Kabupaten Semarang, Jawa Tengah Tahun 2014) - Dewi Sophia; Ronny Aruben; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
One of problem that showed up from commercial sex workers is nutrition rearand mother’s nutrition knowledge that affect nutrition status from the child who was born. Lack of nutrition during pregnancy and the first 2 has a negative consequences. The aim in this research is to analyze the correlation beetwen nutrition rear,mother’s nutrition knowledge as a commesrcial sex workers and nutrition status of children under two yearsin Tegalrejo Prostitution Complex,BergasMunicipality,SemarangRegency,Central Java 2014. This research is qualitative research. Indepth interview with children under two years and with the mother or guardian that raised the child is used as methods in this research. Secondary data that are used such as children under two years visits in January-April 2014 and Immunisation data. The results are 4 children under two years are good nutrition status,2 children are overweight, 1 childern is lack of nutrition and 3 children are under nourished children under two years. The children who are under nourished never given mother’s milk and sincerity rather than children under two years in group overweight and good nutrition status. But, overweight children under tow years are given too much mother’s milk until two years and spoiled especially in fast food. Good coordination between mother or guardian and health facility are needed to accomplish children under two years healthy.